Automated Online Quantification Method for 18F-FDG Positron Emission Tomography/CT Improves Detection of the Epileptogenic Zone in Patients with Pharmacoresistant Epilepsy - Mendes Coelho, Vanessa Cristina; Morita, Marcia E.; Amorim, Barbara J.; Ramos, Celso Darío; Yasuda, Clarissa L.; Tedeschi, Helder; Ghizoni, Enrico; Cendes, Fernando (Frontiers in Neurology, 2017)
Aims: To assess the validity of an online method to quantitatively evaluate cerebral hypometabolism in patients with pharmacoresistant focal epilepsy as a complement to the visual analysis of the 18F-FDG PET/CT exame. Methods: A total of 39 patients with pharmacoresistant epilepsy and probable focal cortical dysplasia (22 patients with frontal lobe epilepsy [FLE] and 17 with temporal lobe epilepsy [TLE]) underwent a pre-surgical evaluation including EEG, video-EEG, MRI and 18F-FDG PET/CT. We conducted the automated quantification of their 18F-FDG PET/CT data and compared the results with those of the visual-PET analysis conducted by experienced nuclear medicine physicians. For each patient group, we calculated Cohen’s Kappa coefficient for the visual and quantitative analyses, as well as each method’s sensitivity, specificity, and positive and negative predictive values. Results: For the TLE group, both the visual and quantitative analyses showed high agreement. Thus, although the quantitative analysis could be used as a complement, the visual analysis on its own was consistent and precise. For the FLE group, on the other hand, the visual analysis categorized almost half of the cases as normal, revealing very low agreement. For those patients, the quantitative analysis proved critical to identify the focal hypometabolism characteristic of the epileptogenic zone. Our results suggest that the quantitative analysis of 18F-FDG PET/CT data is critical for patients with extratemporal epilepsies, and especially those with subtle MRI findings. Furthermore, it can easily be used during the routine clinical evaluation of 18F-FDG PET/CT exams. Significance: Our results show that quantification of 18F-FDG PET is an informative complementary method that can be added to the routine visual evaluation of patients with subtle lesions, particularly those in the frontal lobes.